The Characteristics of Vortex Spray Countercurrent Mass Exchange Device (VSCMED) - Sklabinskyy Vsevolod Ivanovych; Abdullah Jalal Mohammed; Mohammed Nahdim Gasim (Engineering and Technology Journal, 2011)
The article contains the results of the efficiency research of vortex dispersing countercurrent mass exchange device performance. There are recommendations given on the basis of analysis of liquid jet and liquid drops movement to assess the mass exchange surface. Processes and Equipment of Chemical and Petroleum Refineries Department of Sumy State University has carried out a great research to design new constructions of vortex mass exchanged devices with countercurrent flow of gas and drop flows.